Maternal mortality in Mexico- A biological event; A social process - Francisco Javier Posadas Robledo (Archives of Preventive Medicine - Peertechz Publications, 2019)
The 21st century is the century of knowledge, technology, but especially, the full exercise of Human Rights. In Mexico, the right to health protection is embodied in the Political Constitution and imposes on the state and its institutions the obligation to protect this essential right. Regardless of the social, labor or economic status that people keep. The Mexican State has the obligation to guarantee this right in favor of each person and entails a series of benefi ts, which satisfy an individual need, but which entails a collective exercise, which aims to keep people healthy, productive and capable of being productive. And generate welfare and better social capital. Health is considered a prerequisite to achieve impacts that generate social development [1].